The Gradual Warm-Up: The United States Supreme Court's Reliance on Social Science Research in Constitutional Criminal Law and Procedure Opinions, 2001-2015. Issue 12 (1st December 2020) - Bisaccia Meitl, Michele; Leeper Piquero, Nicole; Piquero, Alex
ABSTRACT: The United States Supreme Court, through its published opinions, influences the shape of American civil liberties to a greater degree than perhaps any other institution. The Court's reliance on evidence-based research in reaching their opinions matters and should provide a superior basis for decision-making. It also indicates to scholars whether this same research is of practical value to policy-makers. This study examines the frequency to which the Court cites such research and then breaks down the citations by Constitutional Amendment and type of Court opinion. Results indicate overtime the Court has incrementally increased its use of social science research in its criminal procedure opinions.